A passive direct methanol fuel cell as transducer of an electrochemical sensor, applied to the detection of carcinoembryonic antigen - Liliana Carneiro (2021)
This work describes an electrochemical sensor with a biomimetic plastic antibody film for carcinoembryonic antigen (CEA, an important biomarker in colorectal cancer), integrated in the electrical circuit of a direct methanol fuel cell (DMFC), working in passive mode and used herein as power supply and signal transducer. In detail, the sensing layer for CEA consisted of a Fluorine-doped Tin Oxide (FTO) conductive glass substrate - connected to the negative pole side of the DMFC - with a conductive poly (3,4-ethylenedioxythiophene) (PEDOT) layer and a polypyrrol (PPy) molecularly-imprinted polymer (MIP), assembled in-situ. This sensing element is then closed using a cover FTO-glass, hold in place with a clip, connected to the positive side of the DMFC. When compared with control DMFCs, the power curves of DMFC/Sensor integrated system showed decreased power values due to the MIP layer interfaced in the electrical circuit, also displaying high stability signals. The DMFC/Sensor was further calibrated at room temperature, in different medium (buffer, a synthetic physiological fluid model and Cormay® serum), showing linear responses over a wide concentration range, with a limit of detection of 0.08 ng/mL. The DMFC/Sensor presented sensitive data, with linear responses from 0.1 ng/mL to 100 μg/mL and operating well in the presence of human serum. Overall, the results obtained evidenced the possibility of using a DMFC as a transducing element in an electrochemical sensor, confirming the sensitive and selective readings of the bio (sensing) imprinted film. This integration paves the way towards fully autonomous electrochemical devices, in which the integration of the sensor inside the fuel cell may be a subsequent direction.